Iraq: the day after - Schwartz, Eric P. (Council on Foreign Relations Press, 2003)
Introduction – Humanitarian issues – Structure of post-conflict transitional administration – Key issues in transitional administration – Economic issues – Regional diplomatic and security issues – Conclusion – Additional or dissenting views
2003273879
Keywords: Graue Literatur; Kriegsfolgen; Militärische Intervention; Wirtschaftspolitik; Politisches System; Rechtsstaat; Internationale Wirtschaftsbeziehungen; Irak; USA; Gesellschaftsordnung; Iraq War; 2003-2011; Technical assistance; American; Economic assistance; American; Justice; Administration of; Postwar reconstruction; Irakkrieg 2003; Kriegsfolgen/Wiederaufbau/Konfliktfolgen; Transformation/Transition/Demokratisierung; Iraq War 2003; consequences of war/post-conflict reconstruction/consequences of conflict; transformation/transition/democratization; Iraq